Risk factors and predictors of immune-related adverse events: implications for patients with non-small cell lung cancer. Issue 8 (3rd August 2022) - Issa, Majd; Tang, Joy; Guo, Yizhen; Coss, Chris; Mace, Thomas A.; Bischof, Jason; Phelps, Mitch; Presley, Carolyn J; Owen, Dwight H
ABSTRACT: Introduction: Immune checkpoint inhibitors (ICI) are now utilized as a standard of care treatment for multiple cancers, including in both the metastatic setting as well as in earlier stages of disease. The identification of unique immune-related adverse events (irAE) that occur during ICI treatment has led to intense research to identify potential risk factors and biomarkers that may assist in clinical decision making. Although initial studies in ICI were primarily in advanced stage disease, the use of ICI in earlier stages of disease as adjuvant therapies requires a better understanding of patient risk stratification to mitigate or prevent serious irAE. Areas covered: In this review, we set out to describe the current state of research regarding potential risk factors for irAE in patients with non-small cell lung cancer, as well as explore the barriers to understanding irAE. We review data from irAE that occur in large phase 3 trials and prospective studies focusing on irAE, as well as the many retrospective studies that currently form the bulk of our understanding of irAE.